Erythrocyte aggregation in rheumatoid arthritis: cell and plasma factor’s role - Luquita, A. (2009)
ncrease in erythrocyte aggregation (EA) is pathognomonic for rheumatoid arthritis (RA), and its estimation through erythrocyte sedimentation rate (ESR) is part of DAS 28-4 activity diagnosis, with low correlation with EA and that does not discriminate the contribution of cell factors that increase aggregation. Objective: To analyse cell and plasma factors that might be involved in EA increase, to understand how RA affects blood components, thus modifying blood fluid behavior. Methodology: One hundred women presenting active RA were compared with age-matched controls (C). EA was measured by transmitted light, obtaining two parameters: 2k2n0, characterizing the aggregation process kinetics and s0/n0, estimating aggregates size. Cell factors assays: erythrocyte deformability, by filtration through nucleopore membranes, cell shape, by microscopy, and membrane fluidity by EPR. Plasma: total proteins and CRP, albumin, fibrinogen (Fb), by gravimetry, and IgG and IgM by single radial immuno-diffusion. Results: AR and C (x ± SE). 2k2n0: 31.83 ± 2.84, 23.75 ± 1.91; s0/n0: 0.92 ± 0.05, 0.87 ± 0.04. Rigidity index (RI): 14.79 ± 4.71, 6.92 ± 1.31. Morphological index: 0.28 ± 0.03, 0.30 ± 0.05, n.s. Fb (mg/dl): 382 ± 80, 299 ± 70. IgG (mg/dl): 1580 ± 219, 1296 ± 158; IgM (mg/dl) 233 ± 28, 183 ± 23; albumin (g/dl) 3.84 ± 0.44, 3.77 ± 0.51 n.s. p < 0.05 accepted. Correlations: 2k2n0 vs. Fb r = 0.66; s0/n0 vs. Fb r = 0.51; 2k2n0 vs. Igs r = 0.65; s0/n0 vs. Igs r = 0.56. 2k2n0 vs. RI r = -0.59; s0/n0 vs. RI = -0.52, p < 0.05. Conclusions: Plasma factors, Igs and Fb increased aggregation, since RI is altered, this reduces the process efficiency regarding aggregation. Patients with active RA present an increased EA, with values modifications associated with the activity index DAS 28-4, thus becoming an RA activity indicator.